Clinical profile of carcinoma breast patients in working women population in a metro city - S. V., Murali; B. V., Madhusudhan (International Surgery Journal, 2020)
Background: In India, breast cancer is the second most common malignancy among women next to carcinoma of cervix. Since it present as a painless lump patient often neglect and present to hospital late. With increasing prominence and greater visibility in country specific health profiles around the world, breast cancer and its prevention detection and treatment will continue to emerge as a major priority and challenge for health system. As carcinoma of breast is a quite common clinical problem encountered in clinical practice, this study was an attempt to study clinical presentation modes of management of the disease. Methods: 50 patients who were admitted with a diagnosis of carcinoma breast were studied though history taking, clinical examination, relevant investigations depending on the stage of the disease. After completion, the results were analysed using Microsoft excel software and are compared with other studies. Results: Majority of patients belonging to age group 41-50 years (42%) with lump as major complaint at the time of presentation (78%). Disease in most patients was on upper outer quadrant (78%). Majority of patients belong to stage II (84%) of the disease clinically. Conclusions: The simple and effective methods of detecting the disease early like self-breast examination, clinical breast examination, ultrasonography, mammography, fine needle aspiration cytology should be made aware among the people for early detection and effective treatment of the disease.